Short-term outcomes for lung cancer resection surgery in HIV infection. (1st July 2019) - Sigel, Keith M.; Stone, Kimberly; Wisnivesky, Juan P.; Park, Lesley S.; Kong, Chung Yin; Silverberg, Michael J.; Brown, Sheldon; Goetz, Matthew; Rodriguez-Barradas, Maria C.; Gibert, Cynthia; Shebl, Fatma; Bedimo, Roger; et al.
Abstract : Objective: Lung cancer is the leading cause of cancer death in people living with HIV (PWH). Surgical resection is a key component of potentially curative treatment regimens for early-stage lung cancers, but its safety is unclear in the setting of HIV. From a national cohort, we assessed potential differences in the risk of major lung cancer surgery complications by HIV status. Design: We linked clinical and cancer data from the Veterans Aging Cohort Study (VACS) and Veterans Affairs Corporate Data Warehouse to outcomes from the Veterans Affairs Surgical Quality Improvement Program (VASQIP) and identified 8371 patients (137 PWH, 8234 uninfected) who underwent lung cancer surgeries between 2000 and 2016. Methods: We compared rates of 15 major short-term surgical complications by HIV status. Results: Use of surgical resection for early-stage lung cancer did not differ by HIV status. Lung cancer surgery postoperative (30-day) mortality was 2.0% for PWH and did not differ by HIV status ( P = 0.9). Pneumonia was the most common complication for both PWH and uninfected veterans, but did not differ significantly in prevalence between groups (11.0% for PWH versus 9.4%; P = 0.5). The frequency of complications did not differ by HIV status for any complication (all P > 0.3). There were no significant predictors of postoperative complications for PWH. Conclusions: In a national antiretroviral-era cohort of lung cancer patients undergoing surgical lung resection, short-term outcomes after surgery did not differ significantly by HIV status. Concerns regarding short-term surgical complications should have limited influence on treatment decisions for PWH with lung cancer.